Group Guidance Model to Improve Students’ Resilience in the Covid-19 Era - Bahiroh, Siti; Madjid, Abd. (Universitas Pahlawan Tuanku Tambusai, 2022)
Resilience is an important ability for adolescents to have, because, without resilience, adolescents will have difficulty in living a life that results in not being able to actualize themselves, self-achievement is not optimal and tends to be pessimistic person and can even suffer from depression. The provision of group counselling services is an effort that can be made by the school to improve student school engagement. The purpose of this study was to determine the form of group counselling services in increasing student school engagement during the pandemic. This study uses a literature review method with data collection techniques, namely collecting articles and books from several online journal article bases. The findings from this study indicate that enhancing student engagement in learning at school can be done through the provision of group counselling services using an appropriate strategy.